Spontaneous coronary artery dissection: a focus on post-dissection care for the vascular medicine clinician - Martinez, Katherine A.; Gudenkauf, Brent; Ratchford, Elizabeth V.; Kim, Esther S. H.; Sharma, Garima (Frontiers in Cardiovascular Medicine, 2024)
Spontaneous coronary artery dissection (SCAD) is an uncommon condition which is increasingly recognized as a cause of significant morbidity. SCAD can cause acute coronary syndrome and myocardial infarction (MI), as well as sudden cardiac death. It presents similarly to atherosclerotic MI although typically in patients with few or no atherosclerotic risk factors, and particularly in women. As more patients are recognized to have this condition, there is a great need for clinician familiarity with diagnostic criteria, as well as with contemporary treatment approaches, and with appropriate patient-centered counseling, including genetic testing, exercise recommendations, and psychological care. The standard of care for patients with SCAD is rapidly evolving. This review therefore summarizes the diagnosis of SCAD, epidemiology, modern treatment, cardiac rehabilitation and preconception counseling, and the current approach to genetic testing, exercise recommendations, and psychological care, all of which are crucial to the vascular medicine specialist.